Mapping the relationship between atopic dermatitis and gut microbiota: a bibliometric analysis, 2014–2023 - Wang, Yilin; Wang, Bingkun; Sun, Shiyou; Wang, Zhongzhi (Frontiers in Microbiology, 2024)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin condition affecting 25% of children and 7-10% of adults, impacting both physical health and mental well-being. The stability of gut microbiota influences AD progression through immune modulation, skin barrier integrity, and neuroendocrine signaling, making it a potential target for AD prevention and treatment. This study explores the correlation between AD and gut microbiota, focusing on infants to provide insights into potential strategies. Methods: A search on the Web of Science Core Collection (WOSCC) from January 1, 2014, to December 31, 2023, was conducted. English-language articles and reviews were included. Publications were screened by two investigators, and visual analysis was performed using CiteSpace, VOSviewer, Scimago Graphica, and Microsoft Excel. Results: Of 804 articles included, there was a significant increase in publications over the past decade. The United States, Wageningen University, and University Ulsan (represented by Hong SJ) led in paper count. Nutrients had the most publications, while the Journal of Allergy and Clinical Immunology had the highest citations and centrality among co-cited journals. Keyword analysis identified 'atopic dermatitis' and 'gut microbiota' as central themes. Research focus has shifted from 'Fecal microbiota,' 'caesarean section,' and 'first 6 months' to 'cells,' 'dysbiosis,' and 'prebiotics,' reflecting growing interest in mechanisms and interventions related to intestinal microecology in AD treatment. Conclusion: Research in AD and gut microbiota has evolved, with increased emphasis on understanding interactions between gut microbiota and AD pathogenesis. Recent studies explore various aspects of this connection, offering insights for future research. This review highlights trends and hotspots, serving as a reference for ongoing investigations and suggesting future research directions.